Literarische Formen des Erinnerns : Die deutschsprachige Gegenwartsliteratur zwischen Aufstörung und Stabilisierung - Gansel, Carsten 1955- HerausgeberIn; Möbius, Thomas 1963- HerausgeberIn (De Gruyter, 2024)
The contributions in the volume follow the path of a “rhetoric of memory” in its various forms in the area of tension between canonization and decanonization as well as disruption and stabilization. The fundamental premise is that in the form of literary-narrative productions, individual and generation-specific memories are made available for collective memory and thus become observable. The texts selected for analysis deal thematically with the remembered traumas of the First and Second World Wars; generation-specific experiences, especially of the GDR and the reunification and post-reunification periods, as well as migration experiences in general. The subject of the study are texts by well-known writers such as Jan Koneffke, Zoltán Dany, Michael Niavaranis, Jakob Hein, Steffen Kopetzky, Annett Gröschner, André Kubiczek, Manja Präkels, Robert Menasse, Verena Boos, Assia Djebar, Christoph Hein, Saša Stanišić and Georg Kreisler